Book Review on "This Is How We Talk: A Celebration of Disability and Connection" by Jessica Slice and Caroline Cup - Wardany, Ossy Firstanti (Indonesian Journal of Disability Studies, 2025)
This Is How We Talk: A Celebration of Disability and Connection was written by Jessica Slice & Caroline Cup, illustrated by Kayla Harren. It was published in July 2025 by Dial Books for Young Readers, an imprint of Penguin Random House. Consisting of 48 pages, this book is a picture book aimed at children but can also be enjoyed by adults. In short, this is a colourful and inclusive picture book, showcasing diverse ways of communicating. It is an engaging book for children to read and discuss with their teachers and parents.